Guatemala : First Review Under the Stand-By Arrangement and Requests for Modification of Performance Criterion and Consultation Clause; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guatemala. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the First Review Under the Stand-By Arrangement for Guatemala. The fiscal deficit is increasing owing to a sharp decline in revenues, associated with the contraction in imports and domestic demand. The policy interest rate has been cut. All quantitative performance criteria through June have been met. Inflation has fallen below the consultation band set in the program, triggering a consultation with IMF staff. Fiscal policy needs to continue striking a balance between avoiding a procyclical stance and maintaining debt sustainability.